Nghiên cứu tổng hợp và ứng dụng xúc tác quang của vật liệu Ag-ZnO - Nguyễn Thị Việt Nga; Lê Thị Lệ Quyên; Nguyễn Văn Kim; Võ Viễn (My University, 2016)
Nghiên cứu tổng hợp và ứng dụng xúc tác quang của vật liệu Ag-ZnO
Keywords: Ag-ZnO